PARIWISATA BALI DALAM ERA OTONOMI DAERAH: PELUANGATAUANCAMAN - I Wayan Mertha (JURNAL KEPARIWISATAAN, 2010)
Talented with the uniqueness of art and culture, beautiful nature landscape, and friendly people, Balinese tourism sector has experienced rapid development and constant increasing number of tourist visit. The central government policy on decentralization since 1999 regarding the autonomy of local government in the development process brings about some consequences on Bali as a tourist destination. The central government policy enable the local government to share income generated from physical resources i.e. natural resources. However, it does not include intangible resources such as art and culture which immensely contribute to tourism sector. Therefore, the policy on local government autonomy brings about some disadvantages to Bali.